Význam integrácie simulačných metód do vzdelávania v študijnom programe ošetrovateľstvo – naratívny prehľad - Sováriová Soósová, Mária; Zamboriová, Mária (Ošetrovateľstvo, 2016)
Aim: To outline the purpose and meaning of using simulation methods in education in nursing study program. Background: The transformation of university education is becoming mandatory in medical and paramedical sciences. This transformation is due to the progressive development of health care and medicine informatics, an increase of new knowledge, and advanced diagnostic and therapeutic procedures and well. Methodology: Content analysis of selected studies published in EBSCO databases for the period 2005-2015 and synthesis of collected data. Results: Application of simulation methods (SM) in the learning process in nursing improves cognitive skills of students (knowledge, critical thinking, clinical judgment, and communication skills), psychomotor skills and affective abilities (increased confidence and motivation, improving satisfaction, relieve anxiety) and it has positive impact on outcomes in patients. Conclusion: The groups exposed to simulation demonstrated positive transformation of cognitive and affective abilities and motor skills in clinical practice. Education based on simulations is an effective teaching strategy in nursing.
Keywords: tréninková simulace; Simulation Training; lidé; klinické kompetence; Clinical Competence; Patient Simulation; osoby simulující pacienta ve výuce; studium ošetřovatelství; Education, Nursing; Humans